Psychometric Properties of the Strengths and Difficulties Questionnaire-Dysregulation Profile in Italian Early Adolescents - Valentina Levantini; Eleonora Cei; Gennarina Pirri; Pietro Muratori (MDPI AG, 2021)
Emotional dysregulation is of great cause for concern because it is associated with severe outcomes. Currently, the identification of youths with signs of emotional and behavioral dysregulation is obtained through the assessment of a Dysregulation Profile (DP), including the Strengths and Difficulties Questionnaire-DP (SDQ-DP). Despite its increasingly frequent use in research, studies exploring the SDQ-DP properties are still limited, and no study with Italian samples is currently available. The current study aimed to explore the psychometric properties of the SDQ-DP parent-report and its association with difficulties in the school context in a sample of 332 Italian early adolescents. Results showed that the SDQ-DP parent-report is a single-factor measure with good internal consistency. Also, in both males and females, the SDQ-DP parent-report was associated with higher teacher-reported Internalizing (e.g., anxious symptoms) and Externalizing Problems (e.g., hyperactivity, conduct problems) and lower Prosocial Behavior. This study added further evidence about the utility of the SDQ-DP in the assessment, prevention, and treatment of emotional dysregulation.